ANALISIS ANGGARAN PENDAPATAN BELANJA NEGARA(APBN) TERHADAP PENDANAAN KEBIJAKAN PENDIDIKAN - Muhammad Shalman Al Farizy Santoso (Jurnal Studi Ilmu Pemerintahan, 2021)
The State Revenue and Expenditure Budget or APBN is the annual financial plan of the state government approved by the House of Representatives. The purpose of the preparation of the APBN is as a guideline for state expenditures and revenues so that there is a dynamic balance in carrying out state activities to achieve increased production, increased employment opportunities, high economic growth and ultimately aimed at achieving a just and prosperous material and spiritual society based on Pancasila and the 1945 Constitution. “Indonesia is still behind several Asian countries in terms of education, even though 20 percent of the state budget has been spent on education for the last ten years. This is still not satisfactory. It may even be a disappointment because Indonesian education graduates do not reach the desired level. Equitable access to education and inadequate facilities and infrastructure, especially in Eastern Indonesia and the Disadvantaged, Frontier, Outermost (3T) areas. This is one of the challenges that the government will fix. The results of this research are (1) the process of formulating education funding policies reflects the lack of political will commitment from the government and the DPR. (2) Implementation of the education funding policy of 20% of the APBN. (3) Results of the education funding policy analysis. This study aims to determine how to formulate education funding policies, their implementation and analyze them. The method used in this study is a policy analysis method with a retrospective policy analysis model and the type of policy process analysis.